P27 MONOMORPHIC VENTRICULAR TACHYCARDIA INDUCED BY BLUNT CHEST TRAUMA IN A YOUNG MAN WITHOUT STRUCTURAL HEART DISEASE: A CASE REPORT. (18th May 2022) - Casula, M; De Toni, C; Mameli, S; Schintu, B; Setzu, A; Scalone, A; Pasqualucci, D; Tola, G; Corda, M
Abstract: Introduction: Life–threatening ventricular arrhythmias secondary to chest trauma without structural cardiac damage (i.e. commotio cordis [CC]) are a rare but dramatic cause of sudden cardiac death. We present a case of fast ventricular tachycardia (VT) induced by blunt chest trauma in a healthy man during sports activity. Case Presentation: A 22–year–old man, competitive soccer player, was admitted to our hospital for VT. A few hours before admission, after a heavy ball impact in the chest during a soccer match, he suddenly reported fast and regular palpitation with lightheadedness and dyspnea, without loss of consciousness. The emergency medical service was activated, and the evaluation revealed a hemodynamically tolerated monomorphic VT with a rate of almost 285 bpm (Fig.A ). Amiodaron infusion was ineffective and sinus rhythm (SR) was restored by electrical cardioversion. At the time of admission, he was asymptomatic. Familiar history, past medical history and physical examination were unremarkable. ECG revealed regular SR, with minimal right bundle branch conduction delay (Fig.B ). Blood samples showed normal blood cells count, electrolyte concentrations and liver, kidney, and thyroid function; seriate high sensitivity troponin I determinations were negative. Echocardiography and cardiac magnetic resonance showed normal findings. Computed tomography angiography excluded coronary anomalies. Exercise test revealed no signs of cardiac ischemia and no effort–induced arrhythmias. The fluoroscopy–free unipolar and bipolar voltage maps showed normal electrograms throughout the right ventricle (Fig.C ). No sustained arrhythmias were induced by programmed ventricular stimulation. The patient was then discharged with the indication to cardiology follow–up and the advice to avoid contact sports activities. Discussion: VT is a rare presentation of CC. It has been proposed that CC occurs when a chest strike timed at the upstroke of the T–wave causes both ventricular depolarization trigger and altered dispersion of repolarization, mainly via activation of KATP channels. In the absence of structural heart disease (SHD), the usual presenting rhythm is ventricular fibrillation and there are no accepted mechanisms to explain monomorphic VT in this context. Some authors reported monomorphic VT after chest trauma as the first manifestation of arrhythmogenic cardiomyopathy. Therefore, a careful follow–up will be needed to exclude future development of SHD in this patient.